Simulação computacional e síntese de polímero molecularmente impresso para extração em fase sólida (MISPE) de ciprofloxacina em urina - Marestoni, Luiz Diego [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The worldwide increase in the drug’s use is worrisome and causes environmental impacts mainly by the possibility of bacteria´s gene mutation. The concern with Ciprofloxacin should your application, being used only in severe cases. If bacteria develop resistance to this drug, can probably also develop resistance to other. However, developing analytical methods for drug determination in trace levels is difficult, by the low sensitivity or by the interfering molecules that are not possible to be separated by traditional techniques and which interfere in the more sensitive techniques results. Thus, the development of selective extracting phases to a particular drug has economic and social interests. Molecular Imprinted Polymers show a great alternative to this problem's solution. However, their development has many variables. The best choice for the monomer complex pre - polymerization is crucial for the formation of selective nanocavity. Thus, in this work we apply the semi-empirical quantum computer simulation to understand the interaction of Ciprofloxacin - monomer. We simulated the interaction with a list of 20 monomers more used in the literature. The simulations were performed using the HyperChem ® 8.0.5 software for molecular modeling, OPENEYE ® software package for verification and optimization and MMH with MOPAC 2009 to achieve the quantum energy calculation approach to theoretically predict the best monomer for synthesizing polymer proposed. The MIP was synthesized in bulk using acetonitrile as a solvent, Ciprofloxacin as template molecule, EDMA as cross linker, AIBN as radical initiator and the three monomers that were tested in the simulation to check it. The extraction of ciprofloxacin was performed in a Soxhlet system with a solution of ethanol and acetic acid 9:1 (v / v). The resulting polymer was homogenized and sieved. Rebinding analyzes were performed by isotherms and selectivity tests. The results of isotherms showed that

O aumento mundial na utilização de fármacos é preocupante pelos impactos ambientais causados e principalmente pela possibilidade de mutação genica das bactérias. A preocupação com a Ciprofloxacina se deve a sua aplicação, sendo utilizado somente em casos mais graves, assim se uma bactéria desenvolve a resistência a este fármaco, provavelmente também conseguirá desenvolver resistência aos demais. No entanto, desenvolver métodos analíticos para determinação do fármaco em níveis de traço é difícil, seja pela sensibilidade baixa de algumas técnicas, seja pela presença de interferentes que não são possíveis de serem separados pelas técnicas tradicionais e que interferem no resultado de técnicas mais sensíveis. Desta maneira, o desenvolvimento de fases extratoras seletivas a um determinado fármaco apresenta interesse econômico e social. Os polímeros moleculares impressos apresentam uma ótima alternativa de solução para este problema. No entanto, são muitas as variáveis para seu desenvolvimento, dentre elas a escolha do melhor monômero para o complexo de pré-polimerização é de importância fundamental para a formação da nanocavidade seletiva. Desta maneira, neste trabalho foi desenvolvido a aplicação da simulação computacional quântica semi-empírica para o entendimento da interação da Ciprofloxacina - monômero. Foi simulada a interação com uma lista de 20 monômeros mais utilizados na literatura. As simulações foram realizadas utilizando-se os softwares HyperChem® 8.0.5 para modelagem molecular, pacote de softwares OpenEye® para verificações e otimização e MMH com MOPAC 2009 para realização dos cálculos quânticos de energia de aproximação para prever teoricamente o melhor monômero para sintetizar o polímero proposto. O MIP foi sintetizado em bulk utilizando-se acetonitrila como solvente, Ciprofloxacina como molécula molde, EDMA como agente reticulante, AIBN como iniciador...
Keywords: Quimica analitica; Polimeros; Biomimetismo; Moleculas - Modelos; Ciprofloxacina; Polymers